Physical self-awareness among athletes with physical disabilities and its relationship to anxiety in athletic competition in track and field events in the Republic of Yemen. This study focuses on athletes with disabilities affecting their upper and lower - Mahdi Yahya Al-Houri, Mohammed (sports creativity, 2025)
This study aims to identify the level of physical self-perception among people with physical disabilities in the lower and upper limbs, identify the level of anxiety they experience in sports competition, and identify the relationship between physical self-perception among athletes with physical disabilities in terms of physical appearance, physical strength, physical fitness, athletic performance, and physical self-esteem ) and their anxiety levels during athletics competitions in the Republic of Yemen. The researcher used a descriptive approach in the study, and the study sample consisted of athletes with physical disabilities in the lower and upper limbs who participated in senior athletics competitions, numbering 13 players. The study tools used two scales. The first scale measures physical self-perception and was designed by Fox, and the second scale measures competition anxiety and was designed by Martens. Both scales were translated by researcher Muhammad Hassan Alawi. The most important findings of the study are that there are varying levels of physical self-perception among athletes with physical disabilities, and that there are also varying levels of anxiety among these athletes during competitions. More importantly, the results showed that there is a relationship between the physical self-perception of physically disabled athletes and their anxiety levels during athletics competitions in the Republic of Yemen. In other words, the weaker the physical self-perception of physically disabled athletes, the higher their anxiety levels during sports competitions.